Evaluación de la eficiencia de biodepuración para aguas de pozos profundos en la sabana de Bogotá - Quintana, Germán Melo; Sánchez Leal, Ligia Consuelo; Agudelo López, Edgar (Redes de Ingeniería, 2019)
In this article, the process of biodepuration of water to be used in irrigations of vegetables in Chia Cundinamarca was evaluated. The objective of the project was to evaluate the time and action of phytodepuration with the presence of three species of macrophytes Eichornnia crassipes, Scirpus californicus and Lemna minor that were selected for their easy adaptation characteristics. To carry out the verification of the action of the biosystem, an evaluation process was generated by physical, chemical and microbiological means, in addition to using control groups of Spinacia oleracea cultivated in the study area. It was concluded that the biosystem has a high performance of biodepuration reaching a percentage of removal suitable for agricultural use. Additionally, the system is comfortable against its construction, use and maintenance, responding to the critical situation of the water used for irrigation in this Colombian area.